SOCIO-PSYCHOLOGICAL CHARACTERISTICS OF BEHAVIORAL DISORDERS IN PRIMARY SCHOOL AGED PUPILS - Yadgorovna, Bakhronova Komila (International Journal of Psychosocial Rehabilitation, 2020)
Scientific studies of various psychologists set out various forms of changes in the behaviour of children and teenagers and reveal the importance of the role of family upbringing in shaping methods of behaviour and response.